Cryo-EM structures of intact V-ATPase from bovine brain - Rong Wang (Nature Portfolio, 2020)
The vacuolar-type H+ -ATPases (V-ATPase) hydrolyze ATP to pump protons across the plasma or intracellular membrane. Here authors report two cryo-EM structures of the intact V-ATPase from bovine brain with all the subunits including the subunit H, which is essential for ATPase activity.